Commitment to a Lady’s First WIN : Banking Innovation in the Democratic Republic of Congo - Owuor, Vivian Awiti (World Bank, Washington, DC, 2012)
Doing business is challenging in the Democratic Republic of Congo and presents opportunities for innovative approaches to banking, especially for micro, small, and medium enterprises (MSMEs) - and particularly for women entrepreneurs. But it is getting easier, thanks to innovating banking. This SmartLesson reviews some of the early lessons learned from the ongoing implementation of a Women in Business (WIN) component in a MSME finance project with Rawbank, S.A.R.L, and the second-largest bank in the Democratic Republic of Congo.